Below the Radar: Data, Narratives and the Politics of Irrigation in Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
Emerging narratives call for recognising and engaging constructively with small-scale farmers who have a leading role in shaping the current irrigation dynamics in sub-Saharan Africa. This paper explores whether new irrigation data can usefully inform these narratives. It argues that, for a variety of reasons, official irrigation data in sub-Saharan Africa fail to capture the full extent and diverse nature of irrigation and its rapid distributed growth over the last two decades. The paper investigates recent trends in the use of remote sensing methods to generate irrigation data; it examines the associated expectation that these techniques enable a better understanding of current irrigation developments and small-scale farmers' roles. It reports on a pilot study that uses radar-based imagery and analysis to provide new insights into the extent of rice irrigated agriculture in three regions of Tanzania. We further stress that such mapping exercises remain grounded in a binary logic that separates 'irrigation' from other 'non-irrigated' landscape features. They can stem from, and reinforce, a conventional understanding of irrigation that is still influenced by colonial legacies of engineering design and agricultural modernisation. As farmers' initiatives question this dominant view of irrigation, and in a policy context that is dominated by narratives of water scarcity, this means that new data may improve the visibility of water use by small-scale irrigators but may † Jean-Philippe Venot and Sam Bowers are joint first authors. General comments and other correspondence should be addressed to Jean-Philippe Venot. Correspondence on remote sensing radar analysis should be addressed to Sam Bowers. Water Alternatives-2021 Volume 14
Keywords: African Research